The Basel ultrasonography protocol for assessing hepatosplenic pathologies in Asian schistosomiasis: report of a WHO expert meeting - Joachim Richter; Andreas Neumayr; Amadou Garba-Djirmay; Hiroshi Ohmae; Ralph Aniceto; Xiao-Nong Zhou; Jing Xu; Zhaoyu Guo; An Ning; Edward Mberu Kamau; Francesca Tamarozzi; Hannah Wei Wu; et al. (Infectious Diseases of Poverty)
Abstract Asian hepatointestinal schistosomiasis due to Schistosoma japonicum is prevalent in the Philippines and in Indonesia, while it is close to elimination in China. The second Asian schistosome, S. mekongi, is found in Cambodia and Laos. The main pathology caused by both species is liver fibrosis, which can cause significant morbidity and mortality, mainly due to portal hypertension leading to bleeding from esophageal varices. Ultrasonography was introduced several decades ago as a safe, fast, non-invasive, and relatively inexpensive technique for assessing chronic schistosomiasis-related hepatic pathology in the clinical and field settings. A standardized ultrasound protocol had been established by experts at a WHO-chaired meeting in Cairo, Egypt, in 1990. The peculiarities of sonomorphologic abnormalities caused by S. japonicum and S. mekongi were not sufficiently covered in the Cairo protocol and not addressed at all in the subsequent WHO chaired meeting in Niamey 1996. At a follow-up WHO-chaired meeting in Phnom Pehnh, Cambodia, in 2002, an attempt was made to develop a protocol for Asian schistosomiasis, but a protocol resulting from this meeting has never been published. Although several studies investigated the use of ultrasonography to assess S. japonicum- and S. mekongi-related sonomorphological morbidity across endemic areas the lack of a standardized protocol hampered the characterization of sonomorphologic abnormalities with regard to progression, reversibility, prognosis, and correlation to morbidity. In addition, the comparison of data from different endemic areas and populations remained difficult. Therefore, a WHO-chiared expert meeting took place in Basel, Switzerland in September 2024 with the aim to establish a standardized ultrasound protocol for reporting the pathology caused by S. japonicum and S. mekongi. The proposed protocol is described in this article. Graphical Abstract